Intimate partner relationships and gender norms in Mali: The scope of cash transfers targeted to men to reduce intimate partner violence - Lees, Shelley; Kyegombe, Nambusi; Diatta, Ampa Dogui; Zongrone, Amanda; Roy, Shalini; Hidrobo, Melissa (SAGE Publications, 2021)
Mali has implemented the Filets Sociaux (Jigisémèjiri) program that aims to reduce poverty through cash transfers (CTs) to predominantly male heads of household with accompanying measures. This paper reports on a qualitative study of the effects of the program on intimate partner relationships. In-depth interviews were conducted with men and women in monogamous and polygamous households. Findings revealed that the positive aspects of intimate partner relationships were communication and shared values. However, discussions around decision-making revealed male authority with limited influence by women. Physical violence was reported to be caused by tensions and disputes. Whereas sexual violence was contested, some women described sexual force as violence but men and women asserted that compliance in sexual matters by women was expected. Men also asserted control through preventing women from working outside the home. The CTs were managed by the husband, with some involvement of wives in decision-making about the use of CTs. CTs were reported to reduce household poverty and improve wellbeing, especially for men. There were reports of the effects of the program on IPV, especially in the reduction of physical violence, its effects on sexual violence and controlling behaviour were reported to be limited. Since women are not the primary recipients of the CT, there is limited effect on women’s agency to challenge male authority and control around sexual and financial matters. CTs may be more effective if targeted to women, alongside skill and knowledge strengthening to utilize cash transfers to assert their rights to equality and prevent violence